Photographing Central Asia From the Periphery of the Russian Empire to Global Presence - Gorshenina, Svetlana; Abashin, Sergei; De Cordier, Bruno; Saburova, Tatiana (Welten Süd- und Zentralasiens / Worlds of South and Inner Asia / Mondes de l'Asie du Sud et de l'Asie Centrale, 2022)
The volume demonstrates that photography was the cornerstone of imperial media governance and discourse construction in colonial Turkestan of the tsarist and early Soviet periods. The aim of this volume is to interpret photography as a specific tool that reifies reality, subjectively frames it, and fits it into various political, ideological, commercial, scientific, and artistic contexts.